Supply chain risk mitigation apple chips production process of fuzzy failure mode and effect analysis (Fuzzy FMEA) and fuzzy analytical network process (Fuzzy ANP) - Lita Budiarti; Panji Doeranto; Siti Asmaul Mustaniroh (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Consumer demands for competitive product quality are a challenge for apple chip SMEs. Constraints include the availability of raw materials, difficulty in providing and meeting consumer demand, and damaged products during distribution. This study aims to identify, analyze and determine mitigation strategies for reducing the apple chips supply chain risk. The method used for risk identification and analysis is Fuzzy Failure Mode and Effect Analysis (Fuzzy FMEA), and determining the mitigation strategy uses Fuzzy Analytical Network Process (Fuzzy ANP). The research variables include production, technology, market, human resources (HR), distribution, and institutional and financial risks. The results showed that three risks were identified with the highest ranking, namely the collector level on the market risk variable, the indicator of price fluctuations with an FRPN value of 5.505. The risk of the highest rating at the SME level is the market variable, an indicator of returns for apple chips because they do not meet market quality with an FRPN value of 6.013. At the distribution level, it has the highest FRPN value of 5.833, the distribution variable, an indicator of product damage during the distribution process. Determining mitigation strategies is grouped into seven activities that pose risks: production, technology, markets, human resources, distribution, institutions, and finance.